THE DYNAMICS OF FATHER-SON RELATIONSHIP IN FINDING NEMO MOVIE SCRIPT BY ANDREW STANTON - Wawondatu, Nikita Riana R.; Liando, Nihta V. F.; Lolowang, Imelda S. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this study is to find out the dynamics relationship between father and son, what are the aspects that affect the dynamics relationship between father and son, and also the factors that cause these dynamics to occur from the character of the father (Marlin) and son (Nemo). The research method used in this study is a qualitative method. The data in this study were obtained from the two main characters in Finding Nemo, Marlin and Nemo. Both Marlin and Nemo undergo significant changes in their journey, which depicts profound character growth from the beginning of the movie to the end. At the beginning of the story, Marlin is overprotective of Nemo. As for Nemo, he wants to gain confidence and prove himself. By the end of the story, Marlin becomes more open and caring about Nemo's wishes and dreams. And Nemo gains confidence and courage. At the beginning of the story, Marlin is overprotective of Nemo. As for Nemo, he wants to gain confidence and prove himself. By the end of the story, Marlin becomes more open and caring about Nemo's wishes and dreams. And Nemo gains confidence and courage. The aspects that influence the dynamics are Ego, Shadow, and Persona. The dynamics of Marlin and Nemo's relationship can then be investigated from a psychological standpoint that there are factors such as Communication, Boundary Setting, Education, Protection and Emotional Connection